Comparison of the efficacy of the tension band wiring with eyelet wire versus anatomical locking plate fixation for the treatment of displaced olecranon fractures. (6th December 2021) - Shimura, Haruhiko; Nimura, Akimoto; Fujita, Koji; Kaburagi, Hidetoshi
Background: This retrospective study was conducted to assess the clinical outcome and complications between tension band wiring (TBW) with eyelet wire and locking plate fixation used for the treatment of displaced olecranon fractures. Methods: A total of 58 patients (36 males and 22 females; mean age: 63 years) were reviewed between April 2014 and September 2020. TBW with Ring Pin (RP group) was applied in 24 patients, including 15 Mayo type ⅡA and 9 Mayo type ⅡB patients. Anatomical locking plate (ALP group) was used in 34 patients, including 22 Mayo type ⅡA and 12 Mayo type ⅡB patients. Clinical outcome was evaluated using the Mayo Elbow Performance Score (MEPS), and active range of motion of the elbow and forearm and postoperative complications were reviewed. Results: General characteristic of the patients and the fracture type were similar in the two groups. The mean MEPS values were 96.5 ± 7.3 in the RP group and 94.9 ± 9.4 in the ALP group. The mean elbow flexion arc was 127°±11 in the RP group. The mean elbow flexion arc was 122°±18 in the ALP group. No significant differences in clinical outcomes were observed between the two groups. Complication rates were significantly higher in the ALP group (19/34: 56%) than in the RP group (6/24: 25%). Conclusion: Although there were no statistically significant differences in clinical outcomes between the two groups, the ALP group had a higher proportion of any complication than the RP group.